An extended PMP model to analyze farmers’ adoption of deficit irrigation under environmental payments - Cortignani, R.; Severini, S. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 11pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">The growing policy pressure to reduce water use could lead to the introduction of environmental payments granted on the basis of the amount of water farmers save. This paper proposes an extension of the PMP Röhm and Dabbert approach in order to consider deficit irrigation crop techniques which are not observed in the reference period. The proposed methodology is applied to an Italian irrigated area to evaluate the likely impact of such environmental payments on water use, cropping patterns, adoption of deficit irrigation techniques and economic results on farms. The analysis shows that the considered payments induce farmers to reduce water use, to adopt deficit irrigation techniques and increase economic results. This latter result occurs because the payments counterbalance the negative impact caused by the reduction of water use.